2016
DOI: 10.1039/c5nj01905b
|View full text |Cite|
|
Sign up to set email alerts
|

Mimicking vanadium haloperoxidases: vanadium(iii)–carboxylic acid complexes and their application in H2O2 detection

Abstract: Two vanadium(iii) complexes were synthesized. Hydrogen peroxide was detected by a colorimetric method based on catalytic bromination reactions with the complexes as catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Hence, the colorimetric DL of complex for hydrogen peroxide was calculated and found to be 5.7 × 10 −6 mol l −1 which could be detected the micromolar under the optimal conditions. The values obtained in the above results are comparable to those reported in the literature [21,22].…”
Section: Colorimetric Detection Of H 2 Osupporting
confidence: 92%
“…Hence, the colorimetric DL of complex for hydrogen peroxide was calculated and found to be 5.7 × 10 −6 mol l −1 which could be detected the micromolar under the optimal conditions. The values obtained in the above results are comparable to those reported in the literature [21,22].…”
Section: Colorimetric Detection Of H 2 Osupporting
confidence: 92%
“…Contrarily, the pronounced tendency of the triflusal ester group to hydrolysis in water and alcoholic solutions, likely explains the lack of reported metal coordination complexes for this molecule. Previous studies in coordination chemistry that use HTrf as a reagent, only gave as the end‐product metal‐complexes with the metabolite HTB, but up to now never triflusal complexes …”
Section: Introductionmentioning
confidence: 99%
“…Li et al demonstrated the reactivity of scorpionate oxidovanadium(IV)-carboxylate complexes showing only the modifications observed in the UV/Vis spectra [13], and similar studies were performed for oxidovanadiumpoly (pyrazolyl)boratecarboxylate complexes [14] and a series of oxidovanadium (IV) complexes containing poly (pyrazolyl) borate and organic carboxylic acid as ligands [15]. The literature also showed studies involving kinetic data for copper [5,16] and vanadium complexes [12,[17][18][19][20][21]. These data were achieved by changing the catalyst concentration and obtaining linear plots in which the dependence of the absorbance with the reaction time has been graphed, and the reaction rate constant was calculated.…”
Section: Resultsmentioning
confidence: 92%
“…There are experimental evidence in the literature related to metal coordination complexes, in particular, vanadium derivatives and some copper complexes, but working under different experimental conditions (KBr, phenol red, and catalyst concentrations) and the solvent and the temperature varied in each case [11,12]. Different methodologies were employed, and different types of data were obtained.…”
Section: Resultsmentioning
confidence: 99%